2023
DOI: 10.1093/jpids/piad011
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of MRSA Nasal Surveillance Swabs in Ruling-Out MRSA Infections in Children

Abstract: The utility of methicillin-resistant Staphylococcus aureus (MRSA) nasal surveillance swabs has not been well-described in children. This retrospective, cohort study yielded a negative predictive value of 99.4% for an initial negative MRSA nasal surveillance swab in 165 hospitalized children with a suspected infection and clinical cultures obtained from a likely site of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A recently published study at the Johns Hopkins Hospital identified a NPV of 99.4% for all indications combined in 165 hospitalized children. 9 Similarly, their inclusion criteria was also limited to include only those patients who had a presumed infectious diagnosis and excluded those who received MNS for surveillance. Moreover, they utilized a culture-based MNS test like our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study at the Johns Hopkins Hospital identified a NPV of 99.4% for all indications combined in 165 hospitalized children. 9 Similarly, their inclusion criteria was also limited to include only those patients who had a presumed infectious diagnosis and excluded those who received MNS for surveillance. Moreover, they utilized a culture-based MNS test like our study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their key finding of a high negative predictive value (NPV) (95%) of MNS for all combined indications adds to 2 previously and 1 since published studies in children confirming high NPVs (95.5%-100%) for infections that primarily included lower respiratory tract infections (LRTI) and skin and soft tissue infections (SSTI). [2][3][4][5] We applaud Braga for being able to calculate the first-time infection-specific NPVs of MNS in children with LRTIs [95% (n = 46)], SSTIs [96% (n = 24)] and bone and joint infections (BJIs) [91% (n = 22)]. We concur with their conclusions that MNS in children may have a utility beyond LRTIs including SSTIs and BJIs as well as with their call for more data specifically for those 2 latter infections.…”
Section: What About Hospitalized Children With Osteomyelitis?mentioning
confidence: 99%
“…1 Their key finding of a high negative predictive value (NPV) (95%) of MNS for all combined indications adds to 2 previously and 1 since published studies in children confirming high NPVs (95.5%–100%) for infections that primarily included lower respiratory tract infections (LRTI) and skin and soft tissue infections (SSTI). 2–5…”
Section: To the Editorsmentioning
confidence: 99%